PENANAMAN KARAKTER CINTA TANAH AIR MELALUI KEGIATAN EKSTRAKURIKULER REBANA DI MADRASAH ALIYAH NEGERI DEMAK (Unnes Civic Education Journal, 2022)
Cultivating the character of love for the homeland through tambourine extracurricular activities at Madrasah Aliyah Negeri Demak against the background of foreign culture entering our country. In order for the existence of culture to remain strong, it is necessary for the next generation to instill a sense of love for the homeland. The way that can be taken at school is by integrating the values of local cultural wisdom in the learning process, extracurricular or student activities at school. One of them is through extracurricular at school. The purpose of this study was to examine the cultivation of the character of love for the homeland through extracurricular activities Rebana at Madrasah Aliyah Negeri Demak and to analyze the obstacles experienced in inculcating the character of love for the homeland through extracurricular activities Rebana at Madrasah Aliyah Negeri Demak. The method in this research is descriptive qualitative. The results showed that: the method of instilling the character of love for the homeland through tambourine extracurricular activities at Madrasah Aliyah Negeri Demak using the Habituation Practice Method, Demonstration, Providing Motivation, and the Exemplary method. The inhibiting factors for planting the character of love for the homeland through tambourine extracurricular activities at Madrasah Aliyah Negeri Demak include 1) Internal factors, there are still students who are lazy and bored and lack of focus on students in training, 2) External factors, from their parents, coaches and coaches not always accompanying students during practice, unsupported infrastructure such as tambourines and costumes that need to be repaired, and the training ground is uncertain.